2018
DOI: 10.1002/jcad.12222
|View full text |Cite
|
Sign up to set email alerts
|

Child‐Centered Play Therapy: Aggression, Empathy, and Self‐Regulation

Abstract: The authors conducted a randomized controlled trial to investigate differences among 36 elementary school age children who received 16 sessions of child-centered play therapy and 35 children who were assigned to a waitlist control group. Pre-and postassessments were used to measure children's levels of aggression, self-regulation, and empathy per parent and teacher report. Results revealed statistically significant positive results for parents and nonstatistically significant results for teachers. Implications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 36 publications
1
17
0
2
Order By: Relevance
“…positive regard through growth-promoting relationships to support healing, selfacceptance, and empathy (Wilson & Ray, 2018). These are multicultural humanistic psychologically oriented initiatives that help diverse youth achieve equitable opportunities for holistic health and flourishing.…”
Section: Kazanjianmentioning
confidence: 99%
See 1 more Smart Citation
“…positive regard through growth-promoting relationships to support healing, selfacceptance, and empathy (Wilson & Ray, 2018). These are multicultural humanistic psychologically oriented initiatives that help diverse youth achieve equitable opportunities for holistic health and flourishing.…”
Section: Kazanjianmentioning
confidence: 99%
“…When developmental challenges are not overcome, children experience long-term effects on well-being, where 75% of all mental disturbances are first seen before the person turns 25 years old but are not treated appropriately (Morrish et al, 2018). Longitudinal studies have found children with behavioral and emotional challenges to be at a high risk for long-term behavioral problems, interpersonal issues, difficulties regulating emotions, and academic failures (Wilson & Ray, 2018). When students are taken out of the classroom because of behavioral issues, they miss an average of 20 to 40 min of instruction, have a lower likelihood of academic success, and an increase in developing further behavioral challenges and likelihood of incarceration (Bowers et al, 2017).…”
Section: Under Pressure: Negative Stress and Emotional Challenges In ...mentioning
confidence: 99%
“…An example of DDA being used in counseling research can be found in a study by Wilson and Ray (2018). In this study, the researchers were interested in exploring the effectiveness of child-centered play therapy on children's aggression, selfregulation, and empathy.…”
Section: Descriptive Discriminant Analysismentioning
confidence: 99%
“…With this information, researchers can create a discriminant model that classifies participants into predefined Watson et al groupings based on data collected from each on the predictor variables. Moreover, researchers can evaluate the unique and shared contributions of each dependent variable in accounting for noted differences between groups (Wilson & Ray, 2018).…”
Section: Descriptive Discriminant Analysismentioning
confidence: 99%
“…Other than recommendations of CCPT scholars, no empirically supported guidelines exist regarding the facilitation of parent consultations in CCPT. Ray (2011) developed a manual describing the attitudinal qualities and therapeutic skills play therapists should demonstrate to successfully conduct CCPT sessions, and the effectiveness of these standards has been supported by the manual’s use in multiple research studies (e.g., Bratton et al, 2013; Ray, Stulmaker, Lee, & Silverman, 2013; Swan & Ray, 2014; Wilson & Ray, 2018). By following guidelines provided in the manual, play therapists are provided a structure for specific behaviors they should demonstrate in the playroom in order to increase the effectiveness of CCPT.…”
Section: Implications For Practice Training and Researchmentioning
confidence: 99%